Improving fifth-grade students’ learning outcomes in integrated thematic learning using the RADEC model - Roza, Elvira; Lena, Mai Sri (Journal Of Teaching And Learning In Elementary Education, 2023)
The study was undermined by the low learning results of students in integrated thematic learning in class V SDN 10 Palak Aneh Pariaman. The subjects of this study consist of f 28 fifth-grade students. Research method is a mixed approach, and this type of research is class action research. Data collection techniques were through observation, non-test and test. These results of this study indicate that learning activities and outcomes increases from good to excellent category. From the results obtained, it can be concluded that the application of the RADEC model will increase the level of integrated thematic learning outcomes from students.